Removal of Cr(VI) from Aqueous Solutions Using Powder of Potato Peelings as a Low Cost Sorbent - Farai Mutongo; Olga Kuipa; Pardon K. Kuipa (Bioinorganic Chemistry and Applications)
Potato peels which are a low cost, renewable agroindustry by-product were used for the removal of hexavalent chromium from aqueous effluents. Batch experiments were carried out with an artificial effluent comprising of potassium dichromate in deionised water. The effects of the initial hexavalent chromium concentration, dose of biosorbent, and removal kinetics were explored. An adsorbent dosage of 4 g/L was effective in complete removal of the metal ion, at pH 2.5, in 48 minutes. The kinetic process of Cr(VI) adsorption onto potato peel powder was tested by applying pseudo-first-order and pseudo-second-order models as well as the Elovich kinetic equation to correlate the experimental data and to determine the kinetic parameters. The adsorption data were correlated by the Langmuir and Freundlich isotherms. A maximum monolayer adsorption capacity of 3.28 mg/g was calculated using the Langmuir adsorption isotherm, suggesting a functional group limited adsorption process. The results confirmed that potato peels are an effective biosorbent for the removal of hexavalent chromium from effluent.